EVALUASI BESARAN ALOKASI DAK BIDANG KESEHATAN SUBBIDANG PELAYANAN KEFARMASIAN TAHUN 2011 - 2012 - , Risca Ardyaningtyas ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : In this era of decentralization , access and provision of drugs for people in the local area is the responsibility of local governments. Because the limitations of the local budget makes the central government is obliged to guarantee the availability of drugs in the area. Financing sources of drugs from central and local government have not reached the standard of WHO , 2 dollars per capita. To cover demand of financing drug , Special Fund Budget Allocation (SFBA) proposed state budget that funds given to certain areas to fund special activities that are regional affairs and in accordance with national priorities. General criteria to consider certain areas ( regional fiscal capacity ) , specific criteria ( regional characteristics ) and technical criteria ( policy formulation from Ministry of Health ). Since drug policy from SFBA in 2010 , need to be evaluated. The purpose of the study : to evaluate the amount of SFBA for Pharmaceutical services in 2011 and 2012. Methods: The study used secondary data from 2010 and 2011 consist of 6 (six) factors: fiscal capacity, character of the area, population, poverty , local budget for drugsin and prediction for the remaining stock of the drug. Analysis statistics use chi-square and multiple regression . Qualitative interviews with managers of pharmacy in 2 districts with high financial capability. Results: Result from multiple regression test of the 6 factors used in the allocation of SAF 2011 and 2012 only 3 that really affects the allocation are population, the poor and the prediction of the remaining stock of the drug . However, the highest is population. Result for qualitative with 2 respondents , since got SFBA they reduce local budget for dugs, because the drug financing is sufficient from SFBA. Conclusion: local onwership not understand the health budget in areas that rely on the health budget from central government, where the effeciency of the central budget instability causes reduction budget in central and local.